Avaliação da qualidade do serviço educacional em uma Instituição de ensino superior na visão dos alunos do curso de Direito através da escala Servqual - Freitas, Lizandre Cristina Silva (Universidade do Vale do Rio dos Sinos, 2022)
Marketing involves identifying and satisfying human and social needs, so educational marketing emerged as an option to serve educational institutions in their expectation of staying in the market. In the current competitive environment, higher education institutions (HEIs) increasingly see the need to offer a quality service that will meet the wishes of their school community, with a view to attracting and retaining students. This study aims to analyze the perception of the quality of services at Univag - Centro Universitário de Várzea Grande (MT) from the point of view of law students, using the Servqual Scale. The research answers the following question: what is the perception of law students in relation to the services provided by Univag? The use of the Servqual Scale and the quality of educational services was motivated by the need to know the expectations and desires of the customers of educational institutions, in a scenario of strong changes in the area of education. The methodological approach of the study is quantitative, descriptive, using the inductive method. The type of research regarding the procedure was the survey research end the data collection instrument was the questionnaire, whose target population were Univag law school students, which currently has 1,264 students in theperiod 2022/2. It was found that when using Servqual and its variations, the HEIs can identify possible gaps in the provision of their services and, thus, correct them, in order to meet the expectations of their customers, ensuring their satisfaction; Another aspect of the research is the identification of the company's strengths, which can be used as a competitive advantage over its competitors. It was concluded that the performance of the studied HEI in relation to students' expectations about quality in service demonstrated the existence of gaps in all five investigated dimensions. The intervention proposal was presented, suggesting actions to minimize or completely eliminate the detected gaps.
Keywords: Instituição de ensino superior; Marketing de serviços; Gestão da qualidade no serviço; Servqual; Higher Education Institution; Services marketing; Service quality management; ACCNPQ::Ciências Humanas::Educação